In Vitro And In Vivo Toxicity Of Docetaxel-Loaded Polymeric Nanoparticles Formulation For Potential Treatment Of Lung Cancer - Ahmad Fisol, Faisalina (2022)
Docetaxel is one of chemotherapeutic drug that had been used for treatment of lung cancer for the past two decades. However, the poor solubility of these compounds necessitates the inclusion of surfactant vehicles in their standard solvent system commercial formulations such as Cremophor EL, polysorbate 80 and ethanol. These had led to a number of pharmacologic and biologic effects related to these drug formulations such as clinically relevant acute hypersensitivity reactions and peripheral neuropathy. Hence, the aim of the present study was to prepare, characterize, and evaluate toxicity of poly-ɛ-caprolactone nanoparticles containing anticancer drug, docetaxel (DTX) to in order to improve the efficacy of this chemotherapeutic agent. Poly-ɛ-caprolactone nanoparticles containing DTX (DTX-PCL-NP) were prepared by nanoprecipitation method.